2009
DOI: 10.1016/j.humimm.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between E148Q MEFV variant and Kawasaki disease

Abstract: We investigated a possible association between Kawasaki disease (KD), a systemic vasculitis of unknown etiology, or its coronary artery lesions (CAL) and MEFV gene variants including E148Q, the most common and mild mutation in the MEFV gene for familial Mediterranean fever or vasculitis-related disorders. The study population comprised a total of 138 Japanese patients with KD, including 45 patients with CAL and 93 patients without CAL and 170 normal controls. Sequence variations for the MEFV gene were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Heterozygosity of the R202Q mutation was detected in 48/152 (31.6%) FMF patients and in 47/140 (33.6%) healthy controls (p=0.717, diagnostic odds ratio =0.913, 95% CI 0.560-1.49). Yamaguchi et al (21) reported that R202Q heterozygotes were observed in 7/170 (4.1%) of randomly selected healthy Japanese subjects. They and their families had no episodes of periodic fever similar to FMF.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygosity of the R202Q mutation was detected in 48/152 (31.6%) FMF patients and in 47/140 (33.6%) healthy controls (p=0.717, diagnostic odds ratio =0.913, 95% CI 0.560-1.49). Yamaguchi et al (21) reported that R202Q heterozygotes were observed in 7/170 (4.1%) of randomly selected healthy Japanese subjects. They and their families had no episodes of periodic fever similar to FMF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it seems that it could modulate the severity and exacerbation of vasculitis in affected patients. This hypothesis helps us to better understand Yamaguchi`s study about the functional effect of E148Q and its incompetent effect on inflammation 19. We think that in our one patient with compound heterozygote E148Q-M680I, who developed coronary artery dilatation and micro-aneurysm, combination of pathologic mutation (M680I) resulted in vasculopathy.…”
Section: Discussionmentioning
confidence: 74%
“…Yamaguchi et al reported that E148Q mutation was not associated with the development of KD that occurs in a higher frequency in Japanese children. It is possible that the functional effect of this mutation might be too small to stimulate inflammation for the development of vasculitis in KD 19…”
Section: Discussionmentioning
confidence: 99%
“…A study on 138 children affected by KD did not show an increased risk of KD and/or associated coronaritis among the patients with MEFV mutations, as E148Q, P369S, R408Q [18].…”
Section: Discussionmentioning
confidence: 99%